Species dynamics alter community diversity-biomass stability relationships - Mike Fowler (Ecology Letters, 2012)
Previous ecological theory, developed to support the idea that increasing species diversity stabilizes the variability of total community biomass under fluctuating environments, is underpinned by the assumption that all community members have the same simple, stable intrinsic dynamics – an assumption lacking solid empirical support. By modelling ecosystems composed of species with stable, cyclic and more complex dynamics, we demonstrated when both positive and (for the first time) negative diversity–stability patterns are expected. This extends previous theory, providing new, testable hypotheses for explaining observed empirical patterns. This work is relevant to any field studying coupled deterministic and stochastic processes.